Pengaruh Time Budget Pressure, Kompetensi Dan Independensi Terhadap Kualitas Audit Di Kantor Akuntan Publik - Yeremia Valentino; Murtanto Murtanto; Sekar Mayangsari (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to examine and provide empirical evidence about the influence of time budget pressure, competence and independence on audit quality in public accounting firms. The population of this research is public accountants. Based on the purposive sampling method, the number of research samples was 63 public accountants. Hypothesis testing in this research uses SPSS version 26. The results of this research show that time budget pressure, competence and independence have a positive effect on audit quality.